Translation as Counter-Memory: Mainmise and the Making of a Counter-Culture in Quebec - Carmen Ruschiensky (Belphégor, 2022)
Published in Montreal between 1970 and 1978, Mainmise was the most important periodical associated with the emerging youth counter-culture movement in Quebec. Its editors drew inspiration from themes that formed the cornerstones of the American counter-culture movement – sex, drugs and rock n’ roll – and trips to American hippy meccas like Haight-Ashbury in San Francisco or Greenwich Village in New York. The magazine’s aesthetic was marked by an eclectic mix of typesetting, handwriting, drawings and photographs. It was also a product of translation. With access to images and texts drawn from over 200 publications (as a member of the Underground Press Syndicate), Mainmise’s editors and contributors translated some of the American movement’s key writings and music, adapted the psychedelic graphic styles of its comics and periodicals, and provided a hub for an alternative social network. This paper examines the evolution of Mainmise over three periods of its publication history. Integrating perspectives from translation studies and memory studies, it develops the idea of counter-memory as a translational phenomenon based on re-identification (the construction of alternative collective references through cultural borrowing and transfer) and re-temporalization (the re-inscription of references in a remembered past or utopic future). I will first discuss the emergence of alternative collective references in post-Quiet-Revolution Quebec to then concentrate on Mainmise as a locus of transnational, counter-cultural memory and translation.